The Outcome of Surgeries Performed for Retinal Detachment Associated with Chorioretinal Coloboma - Muhammad Tariq Khan; Farooq Khan; Irfan Aslam (Gandhara University, 2023)
OBJECTIVES To study the outcome of surgeries performed for retinal detachments associated with chorioretinal colobomas. METHODOLOGY This retrospective study enrolled 16 eyes of 16 patients with retinal detachments associated with chorioretinal colobomas. Standard 3-ports 23-gauge Pars plana vitrectomy (PPV) with silicon oil tamponade and endo-laser was performed along the rim of colobomas in all cases. In 4 (25.0%) eyes, buckling was performed with 240 silicon bands and vitrectomy to support the vitreous base. In 12 eyes (75.0%), the natural lens was removed with phaco / lensectomy and intra-ocular lens implantation. RESULTS Out of 16 eyes, the retina was re-attached in 15 eyes (93.75%) after the first operation. One eye needed a second surgery, which was successful anatomically after the second surgery. Mean pre-operative best-corrected visual acuity (BCVA) was 3.36 (±0.52), while 2-weeks post-operative BCVA was 1.92 (±0.88), which was statistically significant (P<.001) improvement. Increased intra-ocular pressure (IOP), silicone oil in the anterior chamber (AC), recurrent retinal detachment, and epiretinal membrane (ERM) formation were some of the complications observed post-operatively. CONCLUSION PPV with endo-laser photocoagulation along the rim of colobomas and silicon oil tamponade is an effective surgical procedure with a statistically significant retinal reattachment ratio and best corrected visual acuity improvement in cases of rhegmatogenous retinal detachment (RRD) associated with chorioretinal colobomas.